Girls can! : smash stereotypes, defy expectations, and make history! - Sebastian, Marissa; Pruden, Tora; Towler, Paige (National Geographic kids., 2020)
Profiles seventy-five women who have made history in leadership, sports, the arts, and the sciences, and features interviews with present-day women who are defying stereotypes and achieving their goals. Includes color and black-and-white photographs, fact boxes, discussion questions, and additional resources.